Pengaruh Ukuran Perusahaan, Kepemilikan Institusional, Profitabilitas dan Laverage Terhadap Enterprise Risk Management - Purwandani, Eranikan Rahma; Wafiroh, Novi Lailliyul (Universitas Gorontalo, 2024)
This study aims to examine the influence of Company Size, Institutional Ownership, Profitability, and Leverage on the disclosure of COSO ERM among companies listed in JII 70 for the period 2020-2022. The method used in this research is quantitative, with Eviews 12 as the analytical tool. The results of this study indicate that Company Size and Leverage do not have a significant impact on ERM Disclosure, while Institutional Ownership has a negative impact on ERM Disclosure, and Profitability has a positive impact on COSO ERM Disclosure.